Angiogenic characteristics of blood outgrowth endothelial cells from patients with von Willebrand disease - Groeneveld, D. J.; Bekkum, T.; Dirven, R. J.; Wang, J.‐W.; Voorberg, J.; Reitsma, P. H.; Eikenboom, J. (Journal of thrombosis and haemostasis, 2015)
Summary Background Endothelial von Willebrand factor (VWF) inhibits angiogenesis. Accordingly, blood outgrowth endothelial cells (BOECs) isolated from von Willebrand disease (VWD) patients showed enhanced in vitro angiogenesis when compared with healthy control BOECs. Characterization of the angiogenic response of VWD BOECs is limited and differences between the different types of VWD have not been investigated in detail. Objectives The aim of this study was to further explore the potential pathogenic effect of VWF mutations on angiogenesis. Methods BOECs were isolated from four healthy individuals, 10 patients with VWD and one heterozygous carrier of a type 2N mutation. Cell migration and tube formation were measured. Results Migration velocity and total tube formation were similar between VWD patients and controls in general. BOECs from the type 3 VWD patient and one type 2B patient showed increased migratory velocity and tube formation compared with BOECs from other patients and healthy controls. Directional migration was impaired in eight out of 10 VWD BOECs and the ability to form tubes was limited to early passage numbers, but not for BOECs from healthy controls. Conclusion BOECs can be a useful tool for ex vivo assessment of endothelial cell function in patients with different types of VWD, but possible limitations, such as early loss of angiogenic capacity, should be recognized. BOECs from most VWD patients consistently showed impairment in the directionality of migration. This is the first report on angiogenic properties of a type 3 VWD BOEC, which showed increased in vitro angiogenesis.